The Application of Educational Game “Word Search” in Improving Students’ Vocabulary of The Fifth Grade Student of SD Negeri 5 Pagaralam - Sherly Marlinda (Cipta Pustaka Nusantara, 2025)
This study examined the effectiveness of the Word Search game in improving vocabulary mastery among fifth-grade students at SD Negeri 5 Pagaralam. A quasi-experimental design with pre-test and post-test control groups was used, involving two purposively selected classes. The experimental group received vocabulary instruction through the Word Search game, while the control group was taught using conventional strategies. Vocabulary tests were administered to both groups, and the results were analyzed using paired and independent sample t-tests at a 0.05 significance level. The paired sample t-test for the experimental group showed a t-obtained value of 15.063, exceeding the t-table value of 2.074 (p = 0.000), indicating a significant improvement between pre-test and post-test scores. The independent sample t-test revealed a t-obtained value of 5.552, greater than the t-table value of 2.021 (p = 0.000), confirming a significant difference between the experimental and control groups. These findings demonstrate that the Word Search game is an effective medium for enhancing vocabulary mastery. Its engaging and interactive format increased motivation, provided repeated exposure to target words, and promoted collaborative learning. The study suggests that integrating educational games into language instruction can enrich learning outcomes and foster a more enjoyable, student-centered classroom environment.